Structures of deoxy- and carbonmonoxy-erythrocruorin - Huber, Robert; Epp, Otto; Formanek, Helmut (Journal of molecular biology, 1970)
The structures of the deoxy and carbonmonoxy derivatives of the insect haemoglobin erythrocruorin have been determined by difference Fourier syntheses. In deoxyerythrocruorin the iron atom of the haem group was found to be five-coordinated. The carbonmonoxy- versus deoxy- difference map showed that the carbon monoxide molecule is inclined to the haem plane. Slight structural changes could be observed to take place on carbon monoxide binding. These structural changes are probably due to the difference in spin state between deoxy- and carbonmonoxy haemoglobin.